`Stop or Íll Call The Police!́ The Idea of Police, or the Effects of Police Encounters Over Time - Proença Júnior, Domício (The British journal of criminology, 2006)
This article develops Bittner's (1974) theory of the police by considering the effect of police encounters over time. It argues that the expectation that the police will intervene whenever called establishes the idea of police' in the public, and how this makes the idea of police a pre-eminent factor in the preservation of law and order in democratic societies. The idea of police' is then applied exploratorily to the results of the Kansas City and Newark Patrol Experiments and for the quasi-experimental' dynamics of Brazil's 1997 police strike, demonstrating its explanatory value. In conclusion, this article argues that the preservation of the idea of police is the paramount concern for police policy and management